A Study of Pharmaceutical Product Registration Process in Cambodia– A First Step Towards Developing a Product-Mix - Dr. Nikunj Patel (Jai Maa Saraswati Gyandayini An International Multidisciplinary e-Journal, 2023)
The Pharmaceutical market in Cambodia attracts high competition due to the fewer entry barriers in the market. The Cambodian medicine requirements are highly dependent on the import of medicines from countries like India, China, Bangladesh, Thailand, Vietnam, and some European countries. India is one of the leading suppliers and contributors to medicine imports in Cambodia due to its cost-effective generic products. In such a competitive market pharmaceutical companies need to constantly introduce new products and dosage forms to be ahead of the competition and capture market share. Any pharmaceutical product imported into Cambodia must be registered at MOH –Cambodia before entering the country. Hence pharmaceutical companies need to focus on the product registration process first, to introduce new products in the market. This descriptive qualitative research concentrates on the first step of creating product-mix offerings –i.e., the new product registration process. The data was collected from one-to-one personal written interviews with the field experts. The current pharmaceutical product registration guideline in Cambodia takes approximately 7 months to register a new POM product. However, companies can opt for fast-track approval by paying an additional official fee determined by the regulators.